Vitamin D-binding protein contributes to COPD by activation of alveolar macrophages. Issue 3 (12th January 2011) - Wood, A M; Bassford, C; Webster, D; Newby, P; Rajesh, P; Stockley, R A; Thickett, D R
Abstract : Background: Vitamin D-binding protein (DBP) genetic polymorphisms have been associated with chronic obstructive pulmonary disease (COPD). DBP has an indirect role in macrophage activation; thus it was hypothesised that DBP is present in the airway and contributes to lung disease by this mechanism. Methods: 471 PiZZ subjects with α1-antitrypsin deficiency (AATD) were genotyped for tag single nucleotide polymorphisms (SNPs) covering the DBP gene ( GC ), together with known functional variants, prior to seeking association with COPD phenotypes. 140 subjects with usual COPD and 480 controls were available for replication. Vitamin D and DBP levels were measured by tandem mass spectrometry and ELISA, respectively, in serum and DBP in the sol phase of sputum in a subset of 60 patients. Concentrations were related to phenotype and to alveolar macrophage activation. Results: rs2070741 was associated with airway bacterial colonisation (p=0.04) and bronchiectasis (p=0.01), as was rs7041 (p=0.03) which also influenced vitamin D concentrations (p=0.01). The GC2 variant predisposed to bronchiectasis in AATD (p=0.04) and protected against COPD (p=0.05); the latter association was replicated in usual COPD versus controls (p=0.04). Circulating DBP related inversely to forced expiratory volume in 1 s (FEV1 ) (p=0.02), in direct contrast to vitamin D, where deficiency related to low FEV1 (p=0.04). Sol DBP related directly to alveolar macrophage activation (p=0.004). Conclusions: The genetic association of DBP with COPD may be mediated by effects on macrophage activation, since DBP relates to FEV1, and affects macrophage activation. Vitamin D effects may be independent of this, relating more strongly to innate immunity.